If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4(2x + -3) = x + -12 + 7k Reorder the terms: 4(-3 + 2x) = x + -12 + 7k (-3 * 4 + 2x * 4) = x + -12 + 7k (-12 + 8x) = x + -12 + 7k Reorder the terms: -12 + 8x = -12 + 7k + x Add '12' to each side of the equation. -12 + 12 + 8x = -12 + 7k + 12 + x Combine like terms: -12 + 12 = 0 0 + 8x = -12 + 7k + 12 + x 8x = -12 + 7k + 12 + x Reorder the terms: 8x = -12 + 12 + 7k + x Combine like terms: -12 + 12 = 0 8x = 0 + 7k + x 8x = 7k + x Solving 8x = 7k + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 8x + -1x = 7k + x + -1x Combine like terms: 8x + -1x = 7x 7x = 7k + x + -1x Combine like terms: x + -1x = 0 7x = 7k + 0 7x = 7k Divide each side by '7'. x = k Simplifying x = k
| x+4+14+19=39 | | 2y+3x+x=840 | | 10+4x=5x+14 | | 13v=78 | | x-6=-5+8 | | 45-c=c+15 | | 45-c=c+30 | | 6(5+8r)-3r=6+3(8-3r) | | 0=x^2+x-7 | | n=-9+30 | | 23b=162 | | -28=2-3(4-3n) | | 5X^2+3X+8= | | -6v=-14 | | 8a^3=p^2 | | 11a=30+8a | | 6x-6-4x=6x-5 | | =-14-6v | | 9b=81 | | -x+4x=18 | | 2(2x-138)=x+24 | | 2x+3(.25x)=55 | | 4x+-8=18 | | 5f=-50 | | 4-6+5x= | | 4=-9 | | -7-(-8)=x | | 10.3x-32=-7x+28 | | (2x-(-4))(3x+(-2))=3-(5-3x)(2x+3) | | =h(a+b) | | -7-6=x | | 10x-11x+3=0 |